A comparative study of biological and metabolic biomarkers between healthy individuals and patients with acne vulgaris: A cross-sectional study protocol. Issue 45 (November 2017) - Kim, Kyuseok; Ha, Injin; Kim, Eunok; Kim, Kyunglee
Abstract : Abstract: Acne is a multifactorial dermatosis, which is influenced not only by hormones but also by the biochemical relationship between them and the pilosebaceous unit. Inflammatory cytokines, chemokines, active oxygen, and zinc are known to be associated with the development of acne. Further, steroid metabolism is known as one of the important factors related to sebum secretion and comedone formation in acne. However, there is a lack of studies comparing these human biomarkers between healthy individuals and patients with acne. In particular, no study has investigated the relationship between human biomarkers and patterns of acne yet. The purpose of this study is to investigate diagnostic human biomarkers in acne by comparing the biological and metabolic biomarkers between healthy individuals and patients with acne and identify the relationship between human biomarkers and patterns of acne. This study is a protocol for a cross-sectional study. Forty healthy participants and 60 patients with acne will be recruited at 1 center. We will collect their blood samples and analyze the molecular biological and metabolic biomarkers (cytokines, chemokines, reactive oxygen species, corticotropin-releasing hormone, zinc, amino acid, 1-carbon metabolite, lipid metabolite, etc.). Further, we will administer questionnaires regarding their diet, sleep, stress, and other factors relating to acne and measure their skin elasticity. The study protocol was approved by the Institutional Review Board of Oriental Medical Hospital at Kyung Hee Medical Center (KOMCIRB-161118-HR-062). Written informed consent will be obtained from all the participants. The trial was registered in the Clinical Research Information Service, Republic of Korea: KCT0002212. This trial will provide evidence regarding diagnostic human biomarkers in acne and the relationship between the human biomarkers and patterns of acne.